2023
DOI: 10.1021/acssuschemeng.3c01533
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Efficient Bioconversion of Crocetin from Zeaxanthin via a Dual-Enzyme System

Abstract: Saffron contains pharmacologic active compounds and a large number of flavor compounds. Both originate from carotenoids by biocatalyzed oxidation. Crocetin in saffron exhibits various attractive bioactivities and could be considered in the treatment of various diseases including cancer, coronary heart disease, and hypertension. However, powerful strategies for the efficient and sustainable source of crocetin are lacking. To address this issue, we demonstrated a one-pot approach to bioconversion of crocetin fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Crocetin and crocin V were successfully produced in engineered E. coli and Saccharomyces cerevisiae, but these strains showed low productivity [7,[61][62][63]. Crocin has also been successfully synthesized in vitro using an enzyme cascade [64]. The authors demonstrated an 80.8% conversion rate of crocetin within 2 h with a yield of 1.48 mg/L/h by optimizing the ratio of enzymes in the system and reducing the accumulation of intermediate byproducts [64].…”
Section: Alternative Sources Of Crocinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crocetin and crocin V were successfully produced in engineered E. coli and Saccharomyces cerevisiae, but these strains showed low productivity [7,[61][62][63]. Crocin has also been successfully synthesized in vitro using an enzyme cascade [64]. The authors demonstrated an 80.8% conversion rate of crocetin within 2 h with a yield of 1.48 mg/L/h by optimizing the ratio of enzymes in the system and reducing the accumulation of intermediate byproducts [64].…”
Section: Alternative Sources Of Crocinsmentioning
confidence: 99%
“…Crocin has also been successfully synthesized in vitro using an enzyme cascade [64]. The authors demonstrated an 80.8% conversion rate of crocetin within 2 h with a yield of 1.48 mg/L/h by optimizing the ratio of enzymes in the system and reducing the accumulation of intermediate byproducts [64]. Clearly, to address the high demand for crocins, there is a need for alternative methods.…”
Section: Alternative Sources Of Crocinsmentioning
confidence: 99%
See 1 more Smart Citation
“…With new advances in in vitro multienzyme cascade reactions and modular combinations of enzyme reactions, numerous researchers have begun to pay close attention to in vitro enzymatic technology for the efficient and accurate synthesis of UDP-Gal. Artificially designed in vitro enzyme cascade platforms have shown significant advantages, including high product yields, shorter mass transfer, faster reaction rates, and higher tolerance to toxic products …”
Section: Introductionmentioning
confidence: 99%
“…Artificially designed in vitro enzyme cascade platforms have shown significant advantages, including high product yields, shorter mass transfer, faster reaction rates, and higher tolerance to toxic products. 16 In the in vitro multienzyme cascade reaction, three main pathways can be employed to synthesize UDP-Gal. 17 The salvage pathway (Scheme 1a) involves the conversion of Gal-1P to UDP-Gal by uridine diphosphate sugar pyrophosphorylase (GalU) in the presence of uridine triphosphate (UTP).…”
Section: Introductionmentioning
confidence: 99%